Information technologies and mathematical modelling : queueing theory and applications : 14th International Scientific Conference, ITMM 2015, named after A.F. Terpugov, Anzhero-Sudzhensk, Russia, November 18-22, 2015, Proceedings /: queueing theory and applications : 14th International Scientific Conference, ITMM 2015, named after A.F. Terpugov, Anzhero-Sudzhensk, Russia, November 18-22, 2015, Proceedings. (2015) - Unknown
No abstract available